Comparison of water consumption of three urban greening trees in a typical arid oasis citiy, northwest China - Keyimu, Maierdang; Halik, Ümüt; Li, Zongshan; Abliz, Abdulla; Welp, Martin (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
In order to ensure sustainable development of arid oasis cities, close attention must be paid to the rational use of limited water resources. Since urban vegetation is one important user of water, urban greening activities should be adapted to local environmental conditions. In this study, one native (Morus alba L.) and two introduced urban greening tree species (Fraxinus sogdiana Bunge and Platanus acerifolia Willd.) were selected in Aksu – a typical oasis city in northwest China. Their stem sap flow velocity (SFV) was determined and diel water consumption was calculated. In the meantime, meteorological variables were recorded to analyze the water consumption strategy of these tree species. The results show that the average SFV of M. alba, F. sogdiana and P. acerifolia were 4.1±0.3 cm h-1, 10.5±0.7 cm h-1 and 22.3±2.6 cm h-1, respectively. SFV was positively correlated with solar radiation (Rs), air temperature (Ta), vapor pressure deficit (VPD) and wind speed (Ws), and negatively correlated with air humidity (RH). Stepwise analysis showed that VPD had the highest impact on SFV of F. sogdiana (R²=0.987) and M. alba (R²=0.887), while the impact of RH was highest on P. acerifolia (R²=0.937). P. acerifolia had the highest sap flow daily accumulation (104±7 L tree-1), F. sogdiana was second (52±4 L tree-1), and third was M. alba (16±2 L tree-1). The water use efficiency (WUE) was M. alba (3.61 mmol mol-1) > F. sogdiana (3.33 mmol mol-1) > P. acerifolia (2.90 mmol mol-1). This study showed that native tree species developed certain adaptation strategies to the arid environment and thus consumed less water. Therefore, we recommend that in tree species selection by landscape planners as well as other decision makers, native tree species should be given priority in future urban greening projects.